2016
DOI: 10.3390/ma9060445
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Elevated Temperature Testing of Fly Ash Based Geopolymer Composites

Abstract: In situ elevated temperature investigations using fly ash based geopolymers filled with alumina aggregate were undertaken. Compressive strength and short term creep tests were carried out to determine the onset temperature of viscous flow. Fire testing using the standard cellulose curve was performed. Applying a load to the specimen as the temperature increased reduced the temperature at which viscous flow occurred (compared to test methods with no applied stress). Compressive strength increased at the elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 29 publications
(30 reference statements)
1
11
0
Order By: Relevance
“…This suggested that there is sintering effect and partial melting due to elevated temperature. The partial melting which allowed the viscous flow to fill pores or voids present in the structure27. The sintering effect caused smaller strength drop in 800 °C compared to other samples.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…This suggested that there is sintering effect and partial melting due to elevated temperature. The partial melting which allowed the viscous flow to fill pores or voids present in the structure27. The sintering effect caused smaller strength drop in 800 °C compared to other samples.…”
Section: Resultsmentioning
confidence: 98%
“…3f. In the other way, the formation of crystalline phases was believed inducing less damage to foamed geopolymers as the porosity provides ‘rooms’ for the expansion, causes less disruption to the final structure and finally reinforces the structures27. The presence of the crystalline phases that remained stable at high temperatures is important for the thermal stability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Geopolymers can be successfully used to increase the fire resistance of materials [42,43]. Figure 6 captures the burning characteristics of developed panels.…”
Section: Resultsmentioning
confidence: 99%
“…GPC has been successfully applied in a number of structural construction applications such as beam, column, slab, tunnel lining, pavement, etc. The main reason relied on the fact that GPC could perform similar mechanical behavior as conventional Portland cement concrete [6,7,8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%